The clinical value of intelligent quantitative measurement of cervical elastography in predicting spontaneous preterm birth during second trimester - HE Biyuan, ZHOU Yuqing, YAO Bingyi, CAO Li, BAO Li (Zhenduanxue lilun yu shijian, 2021)
Objective: To evaluate the performance of cervical elastographic parameters combined with cervical length(CL) in predicting spontaneous preterm birth(sPTB) during second trimester. Methods: A total of 431 singleton pregnancies who received routine prenatal care in our hospital from 1 Jan 2019 and 31 Dec 2020 were included. Accor-ding to pregnancy outcome, subjects were divided into study group(n=31, preterm birth) and control group(n=400, term birth). CL was measured by transvaginal ultrasound, and the cervical elasticity parameters were obtained by elastography, including elasticity contrast index (ECI), hardness ratio (HR), mean strain at internal ostium (IOS), mean strain at external ostium (EOS), the ratio of IOS to EOS (IOS/EOS ). Differences in above ultrasound parameters between the two groups were analyzed. Receiver operating characteristic (ROC) curve analysis was performed to assess the value of the above ultrasound parameters in predicting sPTB. Results: CL was lower but ECI, IOS,IOS/EOS were higher in the study group than those in the control group. ROC analysis indicated that the AUC of IOS/EOS (0.885 as a cut-off value) for prediction of sPTB was larger than those of any other elastographic parameters, with sensitivity and specificity were 73.8% and specificity of 64.2%, and AUC of CL (23.8 mm as a cut-off ) was 0.717, with sensitivity of 71.4% and 74.2%. The combination of IOS/EOS and CL showed better performance for predicting sPTB, with AUC of 0.771 and sensitivity of 83.3%. Conclusions: Cervical elastography can be used to predict sPTB during second trimester, and showes better predictive performance when combined with CL.